Hubungan Self Efficacy Dan Lingkungan Kerja Terhadap Perilaku Minum Obat Pada Pasien Hipertensi Di Badan Pusat Statistik : The Relationship between Self Efficacy and Work Environment on Medication Taking Behavior in Hypertension Patients at the Central Statistics Agency - Nurfitriani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: The incidence of hypertension continues to increase every year and the problems that often occur in hypertensive patients are non-compliance with therapy or treatment, changing lifestyles and complications due to hypertension. This is influenced by the beliefs that individuals have to change their behavior, namely poor drug taking behavior. In addition, one of the factors that also plays a role in drug-taking behavior is the work environment. Methods: The data scale of this study is ordinal scale and uses the chi-square statistical test. The chi-square is one of the non-parametric associative bivariate tests. This means that the non-parametric test is used to see the strength of the relationship between two variables that have an ordinal measurement scale. Results: This study shows that there is a significant relationship between self-efficacy and medication taking behavior with a p-value = 0,002 < 0,05. And there is a significant relationship between work environment and drug taking behavior with a p-value = 0,004 < 0,05. Discussion: There is a relationship between self-efficacy and work environment with medication taking behavior in hypertensive patients of the Central Bureau of Statistics.